2010
DOI: 10.1590/s1516-35982010000600009
|View full text |Cite
|
Sign up to set email alerts
|

Níveis de fósforo disponível e tamanho de partícula do fosfato bicálcico na dieta de poedeiras comerciais de 24 a 58 semanas de idade

Abstract: RESUMO -Um experimento foi conduzido para verificar o efeito de níveis de fósforo e do tamanho de partícula do fosfato bicálcico na dieta de poedeiras comerciais na fase de produção. Utilizou-se um delineamento experimental inteiramente casualizado, em esquema fatorial 2 × 3 com dois tamanhos de partícula do fosfato (fino e granulado) e três níveis de fósforo disponível (0,28; 0,38 e 0,48%), totalizando seis tratamentos, cada um com cinco repetições de oito aves. As dietas experimentais foram isoproteicas, iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Ammerman et al (1995) reported in its work that particle size is a determinant factor in the availability of calcium and phosphorus in the defluorinated phosphates, since the solubility of a phosphate increases as it reduces the particle size of the food. However, work published by Araújo et al (2010) showed that particle size did not influence the variables of laying rate, feed conversion, egg weight, egg mass, percentage and shell thickness, and egg specific gravity of commercial laying hens, indicating that the availability of calcium and phosphorus was not influenced by the granulometry of the food. There was a difference between the direct and indirect methods only for the apparent digestibility coefficients of the calcium sources (P <0.05).…”
Section: Resultsmentioning
confidence: 90%
“…Ammerman et al (1995) reported in its work that particle size is a determinant factor in the availability of calcium and phosphorus in the defluorinated phosphates, since the solubility of a phosphate increases as it reduces the particle size of the food. However, work published by Araújo et al (2010) showed that particle size did not influence the variables of laying rate, feed conversion, egg weight, egg mass, percentage and shell thickness, and egg specific gravity of commercial laying hens, indicating that the availability of calcium and phosphorus was not influenced by the granulometry of the food. There was a difference between the direct and indirect methods only for the apparent digestibility coefficients of the calcium sources (P <0.05).…”
Section: Resultsmentioning
confidence: 90%